Governance, Succession, and Formalization of Management in Family Businesses: (re)organizing the role played by multi-generation families - de Oliveira, Janete Lara (2012)
In the context of a family business, harmonizing organizational objectives and the expectations of a multi-generational business-owning family is no easy task. This work was carried out in order to analyze the governance mechanisms and the succession and formalization processes implemented in a traditional and long running family-owned company, seeking to identify likely levels of interrelation and control in such a company. A qualitative research was conducted through a case study implemented at Randon S/A, which has begun a long and still unfinished restructuring process in the 90’s. Research results indicated that endogenous and exogenous factors, such as growth and internationalization processes, the reformulation of the property structure, the admittance of new shareholders, and entering Level 1 of BOVESPA’s corporate governance index, among others, have influenced the changes that have taken place in the ownership, power, control, and management structures of the company. Strategic decisions made by the owning family included formalizing the management of the companies that comprise the holding, the adoption of governance structures that enable to define ownership, and the reduction of conflicts of interest, as well as the definition of clear succession rules. These elements were corroborated by this research as important components for enabling family business to be long-lasting.Key words: Family-owned business governance. Succession. Professionalization of family-owned companies. Property and control.